Motivasi guru dan pengurusan budaya kolaboratif pengurus pendidikan wanita - Abdul Ghani Abdullah, (penerbit ukm, 2006)
The aim of this study is to identify the practices of collaborative culture management among the women managers in the education sector and its effect towards teacher’s motivation. The collection of data is obtained by using survey method through 73 secondary schools under the management of women principal in Penang and Kedah state. These data are analysed based on the units school analysis level. Findings of descriptive analysis shows the management of collaborative culture are practised by women managers but the focus are mainly towards generating and maintaining the dimension of teacher’s collaborative and leadership. Meanwhile the correlation analysis shows existence of strong and significant relationship between collaborative management culture and teacher’s motivation. Moreover, regression findings shows a continuity of cohesiveness of the management of collaborative culture, the influence and effect on the teacher’s motivation. The contribution of the two variables are different based on the level of teacher’s motivation. The implications are the stages of collaborative culture practices, the education managers should exhibit effective organization in organizational aspects of the dimensions of collaborative culture based on the motivation level.